Frank Holmes, the Arab oil pioneer 1874-1947: Historical study - Al-Shugairi, Ahmed Nehme (Al-Adab Journal, 2022)
The researcher explained the most important stages that New Zealand adventurer and explorer Frank Holmes went through during his career that extended from 1874-1947, and explained the reasons that led him to engage in the field of exploration and the conditions that helped him enter the Arab countries and how he was able to exploit these conditions in order to build a good relationship with the residents The Arab region after learning about their character, customs and traditions and how those circumstances contributed to the establishment of the General Eastern Company in London. And a statement of the most prominent contributors to the establishment of this company and the difficulties they faced in their search for oil. The company pursued a policy of obtaining concessions and then allegiance to other companies in exchange for some profits and returns. If the company is not established for an oil purpose, it is unable to extract and sell oil because of its limited capabilities and limitations. In concealment of this policy, Holmes pursued a good relationship with the sheikhs of the Arab Gulf and proved to them his good intentions from Through bitter experiences he lived with them and an understanding of their nature and their need, which he used to achieve his personal desire to bypass, and through this relationship, he was able to bypass the British administration and its laws that it set in order to prevent its activity in the Arabian Gulf as it is a special area of ​​influence for the Anglo-Persian Company under an agreement called the Red Line Agreement, which has long suffered Including Holmes and obvious obstacle in the ways to achieve ambitious region. Holmes contributed to achieving some achievements in Bahrain, Kuwait, Qatar and Al-Ahsa, which was considered his most prominent investment despite his failure to achieve economic gains and allowing the entry of American economic influence into the region, and he has become the master of the situation to this day.